Menafsir Makna “Jihad” dalam Konteks Kekinian - Didi Junaidi (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
This article aims to explore the meaning of jihad in the perspective of contextual interpretation. In this study, the Mawdlū‘ī (thematic) Tafsir method used to catch a big picture or spirit of text, with the tool as a analysis tool in the form of two approaches, namely: Historical (Historical) and Hermeneutic Approaches. From the results of the study, get conclusion that jihad, which has often been reduced by some people as a war against different beliefs (the others), turns out to have a far more substantial meaning and is relevant to the present context. The meaning of the author is that jihad strives to uphold human values, oppose tyranny, uphold justice. In this case, jihad is broadly interpreted not merely as a war against the enemy, but to fight against injustice, tyranny, social pathoologies such as poverty, ignorance, and most importantly, jihad against oneself.